2019
DOI: 10.1159/000499277
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors of Renal Function in Partial Laparoscopic Nephrectomy in Patients with a Kidney Tumor

Abstract: Background: Laparoscopic partial nephrectomy has proven to be an ideal option for tumors in initial stages, preserving part of the renal parenchyma and reducing the possible risk of glomerular filtration decrease. Objectives: The main objective of this study is to determine the factors that can influence, to a greater extent, renal function deterioration after surgery. Methods: This is an observational, descriptive and longitudinal study. The renal funct ion was calculated using the Chronic Kidney Disease Epid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
1
4
0
1
Order By: Relevance
“…The study also reported that the greater the invasion of the surrounding structure, the greater the tumour Fuhrman Grade. 21 Similarly, our study reported ureteric involvement (13.8%), concurrent stones (15.3%) and cysts (5.6%) as well, which is reported at similar lower percentages in international studies. 22 Our study also compared the patients who had RFTs deterioration with those whose RFTs remained normal post-nephrectomy, and results revealed that the greater the Fuhrman Grade, the more will be chances of RFT deterioration (p=0.003).…”
Section: Discussionsupporting
confidence: 84%
“…The study also reported that the greater the invasion of the surrounding structure, the greater the tumour Fuhrman Grade. 21 Similarly, our study reported ureteric involvement (13.8%), concurrent stones (15.3%) and cysts (5.6%) as well, which is reported at similar lower percentages in international studies. 22 Our study also compared the patients who had RFTs deterioration with those whose RFTs remained normal post-nephrectomy, and results revealed that the greater the Fuhrman Grade, the more will be chances of RFT deterioration (p=0.003).…”
Section: Discussionsupporting
confidence: 84%
“…Previous reports have indicated that aging, diabetes, large tumors, heavy weight, longer WIT, longer surgery time, and high RENAL nephrometry scores influence renal function after partial nephrectomy [ 16 19 ]. Our study did not find a significant association between comorbidities, such as diabetes and postoperative renal function.…”
Section: Discussionmentioning
confidence: 99%
“…(9) Este procedimento consiste em promover uma ressecção da massa renal com margens adequadas e tentar poupar o máximo possível de néfrons. Para obter uma correta extração do tumor, é possível isolar os vasos renais e pinçá-los (veia e artéria juntas ou pinçamento seletivo da artéria) para ressecção da massa sem sangramento (10). Martin et al estudaram os efeitos de diferentes formas de isquemia renal na função renal em pacientes submetidos à nefrectomia parcial minimamente invasiva.…”
Section: Discussionunclassified